THE IMPORTANCE OF TEAMWORK FOR QUALITY IMPROVEMENT IN MEDICAL REHABILITATION - Baščarević, Danijela; Baščarević, Slaviša; Dimitrijević, Sanja; Marković, Jovana; Milošević, Stanislava (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Teamwork is an important instrument of organizational development and quality management. In medical rehabilitation, multidisciplinary teams are a necessity. The results of the analysis of the composition and functioning of a team made up of professionals from different disciplines, as well as of teamwork itself, contribute to the understanding of complex work processes, the integration of roles and activities of team members, and the optimization of team performance, as the ultimate goal. The study aims to determine the level of satisfaction within the team and the factors that contribute to building teamwork and better team performance, in terms of greater effectiveness and a decline in absenteeism. Materials and methods: This cross-sectional study was conducted at the Special Hospital for Cerebral Palsy and Developmental Neurology in Belgrade, in January 2021. It analyzed the characteristics and performance of multidisciplinary teams of health workers and other professionals, functionally distributed in four organizational units. The teams anonymously filled out a specially designed questionnaire. The analyzed characteristics of the teams related to the average number of members in the team, gender structure, length of service, and 11 dimensions of teamwork (purpose, satisfaction, interactions, training, communication, processes, etc.). Performance indicators such as effectiveness (number of patients per team) and absenteeism (number of days of absence from work) were taken from the annual operation report for 2020. Results: The level of satisfaction in terms of belonging to the organizational unit, according to the total scale and all four subscales, was highest among employees in the "B" Infirmary Unit. A statistically predominant number of respondents showed high satisfaction with teamwork, which was the result of satisfaction with team management (91.7%), the functioning of the team (88.1%), the organizational culture (79.8%), and team culture (60.5%). It has been confirmed that a better-structured team achieves better performance, in terms of higher productivity and a decline in absenteeism. Conclusion: The study results indicate the necessary improvements that management should implement in organizing teamwork in order to achieve a higher level of satisfaction with teamwork in all respondents and better performance.